Fiber optics based schemes modeling and simulation of QoS for Wi-Fi scenarios using OPNET modeler - Suhad Hasan Rhaif; Adnan Hussein Ali; Rana K. Abdulnabi; Ali Abdulwahhab Abdulrazzaq (Institute of Advanced Engineering and Science, 2020)
Wireless Fidelity (Wi-Fi) network is created on the IEEE 802.11 standard. Connections for local devices in homes and business arenas are provided by Wi-Fi units. With the growing demand as well as penetration of wireless services, the wireless networks users now assume Quality of Service (QoS) besides performances comparable to what is accessible from secure networks. In this paper, OPNET Modeler is used as module and for the simulation of a fiber optic-based Wi-Fi network within a fixed local area network. The aim of this paper is to evaluate their Quality of service (QoS) performances in terms of Wi-Fi voice-packet delay and End-to-End for both Wi-Fi base fiber and Wi-Fi base line. Many scenarios, with same Physical and MAC parameters, have many subnet networks are implementing with fiber optics baseline in addition to Wi-Fi baseline, were created in the network OPNET simulation tool for obtaining the results. The results of simulation reveal that base line demonstrated more delay than base fiber.